2020
DOI: 10.3390/app10072615
|View full text |Cite
|
Sign up to set email alerts
|

Planar Microwave Resonant Sensors: A Review and Recent Developments

Abstract: Microwave sensors based on electrically small planar resonant elements are reviewed in this paper. By virtue of the high sensitivity of such resonators to the properties of their surrounding medium, particularly the dielectric constant and the loss factor, these sensors are of special interest (although not exclusive) for dielectric characterization of solids and liquids, and for the measurement of material composition. Several sensing strategies are presented, with special emphasis on differential-mode sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 86 publications
0
43
0
Order By: Relevance
“…These materials were successfully used in passive devices like oscillators, multiplexers, filters, metamaterials, antennas, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Even though a large number of dielectrics with suitable properties have been reported [ 10 , 11 , 12 , 13 , 14 , 15 ], their mass production is restricted due to the manufacturing costs and technological limitations.…”
Section: Introductionmentioning
confidence: 99%
“…These materials were successfully used in passive devices like oscillators, multiplexers, filters, metamaterials, antennas, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Even though a large number of dielectrics with suitable properties have been reported [ 10 , 11 , 12 , 13 , 14 , 15 ], their mass production is restricted due to the manufacturing costs and technological limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Genarellil et al used a resonant cavity to evaluate NaCl concentration without microfluidic set-up. The interest of this approach is to obtain a direct estimation of the dielectric properties of the complete sample without dissociating the medium and the pollutant [139]. Very recently, Rossignol et al [140] demonstrated an accurate quantification of chemical species at trace levels in a complex liquid with a microwave sensor.…”
Section: Electromagnetic Rf Platforms For Complex Matter Monitoring and Evaluationmentioning
confidence: 99%
“…These advantages have inspired the use of microwave resonators for various sensing applications including ice sensing 21 38 . Microwave resonator sensors operate by monitoring the interaction between high concentrations of electric field (E-field) and a material under test, allowing for material property changes to be observed in real time 39 . In ice detection studies utilizing resonator structures, the microwave sensors were able to detect the accumulation of ice, the thickness of the accreted ice, and the rate of deposition on their surface.…”
Section: Introductionmentioning
confidence: 99%